Electron Transport Lipids Fold Within Membrane-Like Interfaces - Braasch-Turi, Margaret M.; Koehn, Jordan T.; Kostenkova, Kateryna; Van Cleave, Cameron; Ives, Jacob W.; Murakami, Heide A.; Crick, Dean C.; Crans, Debbie C. (Frontiers in Chemistry, 2022)
Lipoquinones, such as ubiquinones (UQ) and menaquinones (MK), function as essential lipid components of the electron transport system (ETS) by shuttling electrons and protons to facilitate the production of ATP in eukaryotes and prokaryotes. Lipoquinone function in membrane systems has been widely studied, but the exact location and conformation within membranes remains controversial. Lipoquinones, such as Coenzyme Q (UQ-10), are generally depicted simply as “Q” in life science diagrams or in extended conformations in primary literature even though specific conformations are important for function in the ETS. In this study, our goal was to determine the location, orientation, and conformation of UQ-2, a truncated analog of UQ-10, in model membrane systems and to compare our results to previously studied MK-2. Herein, we first carried out a six-step synthesis to yield UQ-2 and then demonstrated that UQ-2 adopts a folded conformation in organic solvents using 1H-1H 2D NOESY and ROESY NMR spectroscopic studies. Similarly, using 1H-1H 2D NOESY NMR spectroscopic studies, UQ-2 was found to adopt a folded, U-shaped conformation within the interface of an AOT reverse micelle model membrane system. UQ-2 was located slightly closer to the surfactant-water interface compared to the more hydrophobic MK-2. In addition, Langmuir monolayer studies determined UQ-2 resided within the monolayer water-phospholipid interface causing expansion, whereas MK-2 was more likely to be compressed out and reside within the phospholipid tails. All together these results support the model that lipoquinones fold regardless of the headgroup structure but that the polarity of the headgroup influences lipoquinone location within the membrane interface. These results have implications regarding the redox activity near the interface as quinone vs. quinol forms may facilitate locomotion of lipoquinones within the membrane. The location, orientation, and conformation of lipoquinones are critical for their function in generating cellular energy within membrane ETS, and the studies described herein shed light on the behavior of lipoquinones within membrane-like environments.